Systems Approaches to City Research and Innovation: Biodiversity, Culture, and Geography - Collier, Marcus (My University, 2026)
Cities face complex challenges in meeting community needs while also addressing multiple sustainability issues. Yet prevailing governance approaches struggle to engage with the complexity of cities as social—ecological—technological systems (SETS). Specifically, biodiversity, culture, geography, and their interactions, are often neglected. In this chapter, we present approaches for planning and governance in the nexus of biodiversity, culture, and geography, highlighting challenges and opportunities in the context of the polycrisis: the interlinked, compounding threats posed by biodiversity loss, climate change, inequity, and injustice. We argue that research and innovation with nature in cities requires understanding and embracing the complexity of cities as urban systems; striving for a nexus understanding highlights the importance of the interrelations and interactions between elements of urban systems. We review the knowledge gaps and challenges identified by the Innovate4Cities initiative reports (see Chapter 2 and 3), and, through the nexus conceptualization, propose four ways forward: (1) adopting integrated frameworks to identify leverage points for innovating cities with nature; (2) progressing narrative shifts to more plural and decolonial understandings of innovations in cities with nature; (3) integrating cultural considerations into urban development, planning, and governance; and (4) learning from diverse urban contexts to inform localized urban research and practice.
A Global Research and Action Agenda on Cities and Climate Change Science: The Innovate4Cities Initiative
PUBLISHED
Keywords: International Development; Smart & Sustainable Planet; BIODIVERSITY; NATURE-BASED SOLUTIONS; Urban Geography; Environment and housing; Globalization; Policy; Social participation